When are Tariff Cuts Not Enough? Heterogeneous Effects of Trade Preferences for the Least Developed Countries* - Forge, Fabien; Garred, Jason; Kwon, Kyae Lim (Université d'Ottawa | University of Ottawa, 2021)
Poor countries export a remarkably narrow range of products. To what extent have trade preferences targeted to the least developed countries (LDCs) changed this situation? We study a large set of recent reforms to the LDC trade preferences offered by OECD countries. Leveraging trade policy variation by importer, exporter, product and year, we show that tariff reductions have increased the prevalence of positive trade flows. However, new flows have been far more likely to emerge in cases with previous ‘export experience’, i.e. where countries already exported the same product to another OECD country, or exported a related product to the same importer. So this wave of tariff cuts for LDCs has resulted in an extension of existing patterns of trade rather than wider export diversification.
Keywords: 2106E; Trade policy; trade preferences; tariffs; least developed countries; exports